أثر الابتكار في تحسين جودة خدمة تطبيقات وسائل الدفع الالكتروني (دراسة حالة عينة من مستخدمي تطبيق بريدي موب بولاية الوادي) - عقاب سهير; حم عيد غزلان; حامد آية الرحمان (جامعة الوادي University Of Eloued, 2025)
تهدف هذه الدراسة إلى التعرف على أثر الابتكار في تحسين جودة خدمات وسائل الدفع الإلكتروني، وذلك من خلال إجراء دراسة ميدانية على مجتمع من مستخدمي تطبيق "بريدي موب" لولاية الوادي. حيث اعتمدت هذه الدراسة على المنهج الوصفي التحليل والاستدلالي واستبيان كأداة رئيسية لجمع البيانات، حيث وُزّع على عينة عشوائية بلغت (454) مستخدمًا. وبعد جمع البيانات، تم تحليلها واختبار الفرضيات باستخدام عدد من البرمجيات الإحصائية، شملت: SPSS25، Excel 2016. توصلت الدراسة في شقّيها النظري والتطبيقي، إلى مجموعة من النتائج وكان من أهمها: الابتكار يلعب دورًا مهمًا ومؤثرًا في تحسين جودة خدمات وسائل الدفع الإلكتروني، حيث يُساهم في تطوير تصميم التطبيقات لجعلها أكثر سهولة وجاذبية، ويعزز تفاعل المستخدمين مع الخدمات الرقمية، بالإضافة إلى تحسين مستويات الأمان وحماية البيانات، مما يرفع من مستوى رضا المستخدمين وثقتهم. "This study aims to explore the impact of innovation on improving the quality of electronic payment services through a field study conducted on a population of users of the ""Baridi Mob"" application in the Wilaya of El Oued. The study adopted a descriptive, analytical, and inferential methodology, using a questionnaire as the primary tool for data collection. The questionnaire was distributed to a random sample of 454 users. After collecting the data, the responses were analyzed, and the hypotheses were tested using statistical software such as SPSS 25 and Excel 2016. The study, in both its theoretical and empirical dimensions, yielded several findings. The most important is that innovation plays a vital and influential role in enhancing the quality of electronic payment services. It contributes to developing the application’s design to make it more user-friendly and appealing, strengthens user interaction with digital services, and improves levels of security and data protection, which lead to increased user satisfaction and trust."
ماستر
Keywords: ابتكار، إبداع، تكنولوجيا معلومات والاتصال، جودة الخدمة، وسائل الدفع الالكتروني، تطبيق بريدي موب.; Innovation; Creativity; Information and Communication Technology (ICT); Service Quality; Electronic Payment Methods; Baridi Mob application.